(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
Through this study researcher wants to find relationship between two dependent variables, i.e., hegemonic culture and international multiculturalism with that of independent variable, i.e. Indian higher education system. Since it becomes very important to know what effect multiculturalism and hegemonic culture have on our higher education system so that we can have more culturally responsive classroom practices in place. For this research, data was collected from university level teachers working at various positions like Professors, Associate professors, and Assistant professors. Full-time college faculty members made up the bulk of the data collecting samples. The information was gathered using a survey. All dependent variables i.e., hegemonic culture (0.010), international multiculturalism (0.02) have significant positive impact on the independent variable i.e., Indian Higher Education system, it was also observed that hegemonic culture (0.010) have the least impact on Indian higher education system. We see CRT in educational environments as all about leveraging diverse ethnic groups’ culture and experiences to educate more effectively. A culturally responsive classroom must allow children to keep maintaining both their academic success and their cultural identity. This research contributes towards a theoretical framework which is based on CFA Modelling of construct variables. In this we try to find out relationship between dependent variables like hegemonic culture, what is the role of an experienced teacher in facilitating culturally diverse classrooms and international multiculturalism on independent variable i.e., Indian higher education system.